2022
DOI: 10.1101/2022.11.22.517608
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metabolic consequences of polyphosphate synthesis and imminent phosphate limitation

Abstract: Cells stabilize intracellular inorganic phosphate (Pi) to compromise between large biosynthetic needs and detrimental bioenergetic effects of Pi. Pihomeostasis in eukaryotes employs SPXs domains, which are receptors for inositol pyrophosphates. We explored how polymerization and storage of Pi in acidocalcisome-like vacuoles supports S. cerevisiae metabolism and how these cells recognize Piscarcity. Whereas Pistarvation affects numerous metabolic pathways, beginning Piscarcity affects few metabolites. These inc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 111 publications
(165 reference statements)
1
1
0
Order By: Relevance
“…42−44 In addition, Kim et al reported that phosphate starvation led to reduced accumulation of phosphate-containing nucleotides, nucleoside diphosphates, and nucleoside triphosphates. 45 The results of this study confirm this point. Therefore, increasing the availability of phosphate through supplementation of the fermentation medium and stimulating uptake through phosphate transporters in the HNAC mutant strain can be an effective strategy for enhancing RNA production.…”
Section: Enhancement Of the Expression Of Two Transcription Initiatio...supporting
confidence: 77%
“…42−44 In addition, Kim et al reported that phosphate starvation led to reduced accumulation of phosphate-containing nucleotides, nucleoside diphosphates, and nucleoside triphosphates. 45 The results of this study confirm this point. Therefore, increasing the availability of phosphate through supplementation of the fermentation medium and stimulating uptake through phosphate transporters in the HNAC mutant strain can be an effective strategy for enhancing RNA production.…”
Section: Enhancement Of the Expression Of Two Transcription Initiatio...supporting
confidence: 77%
“…In support of our findings, it has recently been reported that S. cerevisiae lacking polyP shows P i starvation features already under P i − -replete conditions. Based on their metabolomics studies, the authors concluded that vacuolar polyP supplies P i for metabolism even when P i is abundant ( 57 ). A reciprocal relationship between ATP and polyP in eukaryotic cells, and a regulatory connection between their relative abundance and synthesis affecting cellular phosphate homeostasis and primary metabolism, have also been reported by others ( 58 ).…”
Section: Discussionmentioning
confidence: 99%